Effect of Sodium Chloride on the Micellization of Sodium Dodecyl Sulphate in Water and Methanol-Water systems - Niraula, Tulasi Prasad; Chatterjee, Sujeet Kumar; Bhattarai, Ajaya (Himalayan Journal of Science and Technology, 2017)
Abstract available on the full text PDF.